Sensuous scholarship - Stoller, Paul (Contemporary ethnography., 1997)
In Sensuous Scholarship Paul Stoller challenges contemporary social theorists and cultural critics who - using the notion of embodiment to critique both Eurocentric and phallocentric predispositions in scholarly thought - consider the body primarily as a text that can be read and analyzed. He argues that this attitude is in itself Eurocentric and is particularly inappropriate for anthropologists, who often work in societies in which the notion of text, and textual interpretation, is foreign. In many of these societies not only are reading and writing unimportant but vision is not the central perceptual mode. Instead, the "lower" senses are central to the metaphoric organization of experience. Throughout Sensuous Scholarship Stoller argues for the importance of understanding the "sensuous epistemologies" of many non-Western societies so that we can better understand the societies themselves and what their epistemologies have to teach us about human experience in general